EVALUASI KUALITAS PASIR PADA PROYEK BANGUNAN PEMERINTAH DENGAN METODE STATISTIK INFERENSIAL - Dedy Rifabi; Jauhar Fajrin; Buan Ansari (INFO-TEKNIK, 2019)
Sand is one of the key material in civil engineering, which is sometime overlooked during the construction process. In many projects, the first concern is about the structure and then the material. The improper use of material doesn’t show significant signs in the early stage of building service. Using low quality material may give significant impact after few years and when it comes to a concern, it’s always too late to be repaired. Sand has drawn many attentions in term of its quality and few works dealing with this topic have been reported. This study aims to asses the quality of sand collected from few government building projects in west Lombok. The results were analysed using statistic software, which is SPSS 16.0, to provide inferential analyses. A mixed model, namely field surveys and laboratory experiments, were employed for the research methodology. It was found that only one out of the seven project that used proper sandmin terms of quality. The rest do not meet the standards required by SNI (Indonesian Nasional Standard) for sand material. It was also found that the quality of sand used by the observed projects under this research was significantly differ from each other, in terms of their bulk density, apparent specific density, SSD specific density, water absorption, silt content, loose content weight, solid fill weight, and fine modulus. It is strongly recommended that the government should take a good control to the sand suppliers/providers as well as the builders especially when they are involving in the government projects.